ANALISIS KUALITAS PELAYANAN PENDAFTARAN BPJS TERHADAP KEPUASAN PASIEN RAWAT JALAN DI RSUD DOLOKSANGGUL KECAMATAN DOLOKSANGGUL KABUPATEN HUMBANG HASUNDUTAN TAHUN 2024 - Sinaga, Megasilvia; Purba, Dewi; Pakpahan, Sri Imelda (Sekolaah Tinggi Ilmu Kesehatan (STIKes) Kesehatan Baru Doloksanggul, 2024)
Quality health services will provide satisfaction to patients who leave the hospital. Factors that affect patient satisfaction include physical evidence (tangibility), responsiveness (responsiveness), caring attitude (emphaty), assurance (assurance), and reliability (reliability). The purpose of this study is to find out the relationship between patient satisfaction and tangibility, responsiveness, emphaty, assurance, and realibility. This type of research is quantitative research. The population in this study is all outpatient BPJS patients at the Doloksanggul Regional General Hospital. The sample size of the study was 100 respondents using the accidental sampling technique with the slovin formula. The data collection technique was carried out by distributing questionnaires. The analysis used was univariate and bivariate analysis. Tested using the Chi-Square test. The results of the study showed that in the tangibility variable (physical evidence), 85% of respondents rated physical appearance as good and 15% rated it as poor. In the responsiveness variable, 87% of respondents felt a quick response and 13% felt a slow response. On the emphaty variable, the majority of respondents felt 84% concerned while only 16% felt less caring. In the Assurance variable, 88% of respondents felt that they received good security guarantees and 12% felt that they were not good. In terms of reability, 87% of respondents rated reliability as high, while 13% rated it low. Bivariate analysis obtained a p-value of <0.05, which is 0.000 for the variables tangibility, responsiveness, emphaty, assurance and realibility with outpatient satisfaction. Therefore, it can be concluded that there is a significant relationship between the variables of tangibility, responsiveness, emphaty, assurance and realibility with outpatient satisfaction at Doloksanggul Hospital. It is hoped that health workers will continue to maintain the quality of BPJS registered health services so that patient satisfaction is better.